PERFORMANCE TRAITS, BLOOD BIOCHEMISTRY, IMMUNE RESPONSE AND ECONOMIC APPRAISAL OF BROILERS FED DIFFERENT LEVELS OF POULTRY BYPRODUCTS COMPOST - M. T. Khan; S. Mehmood; A. Mahmud; K. Javed (Journal of Animal and Plant Sciences, 2019)
The effect of including poultry house byproducts compost in the diet of broiler chickens was evaluated. A total of 300 newly hatched broiler chicks (Cobb-500) were randomly stratified to five treatment groups in a completely randomized design. Compost was added at four different concentrations i.e. 0, 2.5%, 5%, 7.5%, and 10%. Treatment without any addition of compost (0%) was kept as control. Performance traits, blood biochemistry, immune antibody response, and economic appraisal of broiler chickens were monitored for a period of 35 days. Addition of compost in broiler diet had no effect on feed intake (FI), live weight gain (LWG), feed efficiency (FE), and mortality of birds (P>0.05). Increase in compost inclusion level (10%) caused a marked decrease in abdominal fat content compared to control and 2.5% compost diet. However, carcass yield and relative weights of breast, thigh, wing, liver, gizzard, and heart were not significantly different across treatments (P>0.05). Similarly, there were no differences in serum biochemical indices and immune-related parameters in birds fed the different diets. Birds fed the 10% compost diet, however, showed the lowest feed cost per kg weight gain compared to those fed the control diet (P>0.05). These results indicate that compost can be utilized at levels up to 10% in broiler diets without any detrimental effects on performance traits, serum biochemistry, and immune response. Furthermore, the utilization of compost as a feed resource may reduce feed cost (FC) per kg live weight gain.
Keywords: broiler; poultry byproducts compost; growth performance; immune response; economic appraisal